Quality evaluation of calamansi (Citrus microcarpa Bunge) concentrate with alternative sweeteners - Amora , Karen Joy D. (2004.)
The effect of alternative sweeterners on the quality of calamansi concentrate was investigated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Calamansi; Citrus microcarpa